Polymorphic MLH1 and risk of cancer after methylating chemotherapy for Hodgkin lymphoma. Issue 3 (24th October 2007) - Worrillow, L J; Smith, A G; Scott, K; Andersson, M; Ashcroft, A J; Dores, G M; Glimelius, B; Holowaty, E; Jackson, G H; Jones, G L; Lynch, C F; Morgan, G; et al.
Abstract : Background and objective: Methylating agents are effective chemotherapy agents for Hodgkin lymphoma, but are associated with the development of second primary cancers. Cytotoxicity of methylating agents is mediated primarily by the DNA mismatch repair (MMR) system. Loss of MLH1, a major component of DNA MMR, results in tolerance to the cytotoxic effects of methylating agents and persistence of mutagenised cells at high risk of malignant transformation. We hypothesised that a common substitution in the basal promoter of MLH1 (position -93, rs1800734) modifies the risk of cancer after methylating chemotherapy. Methods: 133 patients who developed cancer following chemotherapy and/or radiotherapy (n = 133), 420 patients diagnosed with de novo myeloid leukaemia, 242 patients diagnosed with primary Hodgkin lymphoma, and 1177 healthy controls were genotyped for the MLH1 -93 polymorphism by allelic discrimination polymerase chain reaction (PCR) and restriction fragment length polymorphism assay. Odds ratios and 95% confidence intervals for cancer risk by MLH1 -93 polymorphism status, and stratified by previous exposure to methylating chemotherapy, were calculated using unconditional logistic regression. Results: Carrier frequency of the MLH1 -93 variant was higher in patients who developed therapy related acute myeloid leukaemia (t-AML) (75.0%, n = 12) or breast cancer (53.3%. n = 15) after methylating chemotherapy for Hodgkin lymphoma compared to patients without previous methylating exposure (t-AML, 30.4%, n = 69; breast cancer patients, 27.2%, n = 22). The MLH1 -93 variant allele was also over-represented in t-AML cases when compared to de novo AML cases (36.9%, n = 420) and healthy controls (36.3%, n = 952), and was associated with a significantly increased risk of developing t-AML (odds ratio 5.31, 95% confidence interval 1.40 to 20.15), but only in patients previously treated with a methylating agent. Conclusions: These data support the hypothesis that the common polymorphism at position -93 in the core promoter of MLH1 defines a risk allele for the development of cancer after methylating chemotherapy for Hodgkin lymphoma. However, replication of this finding in larger studies is suggested.